O niektórych aspektach polsko-rosyjskiego dialogu międzykulturowego: „rossica” w strategicznej pozycji tekstu gazetowego - Sarnowski, Michał (Studia Rossica Posnaniensia, 2010)
In this article the Russian words and phrases playing the role of Polish newspaper headlines are discussed. They are considered here from the point of view of their typology and grammatical correctness.